(untitled) (Bangladesh Journal of Botany, 2019)
A greenhouse experiment was conducted to investigate the effects of water deficit on growth and physiological parameters of Ficus benjamina and Conocarpus erectus. The results revealed that all growth parameters such as plant height, stem diameter, no. of leaves, no. of branches and chlorophyll contents significantly decreased under water deficit condition. Interestingly, although leaf, stem and total biomass production and allocation decreased significantly under water deficit, but root biomass production and allocation increased significantly. Similarly, stomatal conductance to water vapor decreased significantly and CO2 assimilation rate remained similar to control under water deficit condition. Resultantly, a significant increase in water use efficiency was evident in both species under water deficit condition. These results suggested that, in spite of a significant decrease in biomass production, young Conocarpus erectus and Ficus benjamina can tolerate water deficit which is due to sustained CO2 assimilation rate and increase in root biomass.